Charged Particle Therapy with Mini-Segmented Beams - Dilmanian, F. Avraham; Eley, John G.; Rusek, Adam; Krishnan, Sunil (Frontiers in Oncology, 2015)
One of the fundamental attributes of proton therapy and carbon ion therapy is the ability of these charged particles to spare tissue distal to the targeted tumor. This significantly reduces normal tissue toxicity and has the potential to translate to a wider therapeutic index. Although, in general, particle therapy also reduces dose to the proximal tissues, particularly in the vicinity of the target, dose to the skin and to other very superficial tissues tends to be higher than that of megavoltage x-rays. The methods presented here, namely “Interleaved carbon minibeams” and “Radiosurgery with arrays of proton and light ion minibeams”, both utilize beams segmented into arrays of parallel “minibeams” of about 0.3 mm incident beam size. These minibeam arrays spare tissues, as demonstrated by synchrotron x-ray experiments. An additional feature of particle minibeams is their gradual broadening due to multiple Coulomb scattering as they penetrate tissues. In the case of interleaved carbon minibeams, which do not broaden much, two arrays of planar carbon minibeams that remain parallel at target depth, are aimed at the target from 90º angles and made to “interleave” at the target to produce a solid radiation field within the target. As a result the surrounding tissues are exposed only to individual carbon minibeam arrays and are therefore spared. The method was used in four-directional geometry at the NASA Space Radiation Laboratory to ablate a 6.5-mm target in a rabbit brain at a single exposure with 40 Gy physical absorbed dose. Contrast-enhanced magnetic resonance imaging and histology six month later showed very focal target necrosis with nearly no damage to the surrounding brain. As for minibeams of protons and light ions, for which the minibeam broadening is substantial, measurements at MD Anderson Cancer Center in Houston, Texas, and Monte Carlo simulations showed that the broadening minibeams will merge with their neighbors at a certain tissue depth to produce a solid beam to treat the target. The resulting sparing of proximal normal tissue allows radiosurgical ablative treatments with smaller impact on the skin and shallow tissues. This report describes these two methods and discusses their potential clinical applications.